Training Preceptors of Obstetrics-Gynecology Residents through the One-minute Preceptor Model - Machado, Michelle Araújo; Medeiros, Elaine Lira (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective To analyze the effect of the One-minute Preceptor model for preceptors who work at the emergency department of a maternity teaching hospital.Methods  A quantitative intervention study conducted with Obstetrics and Gynecology residency preceptors at a maternity teaching hospital in northeastern Brazil. Three stages were performed: 1) a preintervention survey with the residents; 2) planning and execution of a pedagogical training course for the preceptors, which involved a lecture and a dramatization about the One-Minute Preceptor model; and 3) thirty days after the intervention, the residents answered another survey about the model and its repercussions and advantages.Results The preintervention assessment with the residents showed that 91.7% agreed that there were discrepancies regarding the teaching model among the preceptors. After the training, all preceptors agreed that the model engages the student in the decision-making process, and that they would apply it to their routine. The postintervention results showed that 95.8% agreed that the model is more inviting than traditional teaching approaches. There was a perception of improvement in learning among 70.9% of the residents. In addition, the present study found a significant change in feedback before and after implementing the model, from 20.8% to 66.7%.Conclusion The training course of preceptors in the One-Minute Preceptor model proved to be efficient in providing formative feedback to residents in the emergency department of a maternity school. Further studies are needed to assess the consolidation of the methodology in the long term.
Keywords: preceptorship; training courses; internship and residency; formative feedback; medical education